2014
DOI: 10.1007/s10943-014-9856-9
|View full text |Cite
|
Sign up to set email alerts
|

The Santa Clara Strength of Religious Faith Questionnaire (SCSORF): A Validation Study on Iranian Muslim Patients Undergoing Dialysis

Abstract: The Santa Clara Strength of Religious Faith Questionnaire (SCSORF) is an often used and validated scale that is uncommonly utilized in culturally diverse populations. The purpose of this research investigation was to adapt the SCSORF for use among Iranian Muslim patients undergoing dialysis and to examine the reliability and validity of the scale among this population. A total of 428 patients (228 females, 200 males, M age = 52.2 years, SD = 10) were selected from five dialysis center in Tehran and Qazvin, Ira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…The unidimensional structure of the original (10 items) and brief (5 items) version of the SCSRFQ in Spanish had an adequate fit, and all items loaded significantly on the latent factor religious faith strength, both in the total sample and in the gender and age subgroups. Therefore, the present study replicates previous findings reported in the literature (Akin et al 2015;Cummings et al 2015;Dianni et al 2014;Freiheit et al 2006;Koukounaras et al 2021;Lewis et al 2001;Pakpour et al 2014;Plante and Boccaccini 1997;Plante et al 1999;Plante et al 2002;Plante 2021;Sherman et al 1999;Sherman et al 2001;Wnuk 2017). Thus, each item would reflect only one latent construct and not another (Gefen 2003).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The unidimensional structure of the original (10 items) and brief (5 items) version of the SCSRFQ in Spanish had an adequate fit, and all items loaded significantly on the latent factor religious faith strength, both in the total sample and in the gender and age subgroups. Therefore, the present study replicates previous findings reported in the literature (Akin et al 2015;Cummings et al 2015;Dianni et al 2014;Freiheit et al 2006;Koukounaras et al 2021;Lewis et al 2001;Pakpour et al 2014;Plante and Boccaccini 1997;Plante et al 1999;Plante et al 2002;Plante 2021;Sherman et al 1999;Sherman et al 2001;Wnuk 2017). Thus, each item would reflect only one latent construct and not another (Gefen 2003).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies, in different cultural contexts, have shown that the SCSRFQ is a unidimensional measure of religious faith, with adequate reliability, that presents significant relationships with other variables such as religious life and orientation, intrinsic religious motivation, social provisions, social desirability, anxiety, emotional control, self-righteousness, optimism, spiritual experience, religious coping, negative and positive affect, religiosity and spirituality, spiritual well-being, depression and life satisfaction, among others (Akin et al 2015;Cummings et al 2015;Dianni et al 2014;Freiheit et al 2006; Koukounaras Liagkis and Ktenidis 2021; Lewis et al 2001;Pakpour et al 2014;Plante and Boccaccini 1997;Plante et al 1999;Sherman et al 1999;Sherman et al 2001;Wnuk 2017). Seeking to facilitate the use of the SCSRFQ in epidemiological research and the evaluation of patients with medical illnesses, a study conducted with samples of university students, women with cancer or cancer screening patients, and healthy women in a clinical setting developed a brief version consisting of items 2, 4, 5, 8, and 10 of the original questionnaire (SCSRFQ-SF;Plante et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When items are summed, higher scores indicate greater religious faith. The SCSORF has acceptable internal consistency and validity when used in Persian-speaking people (Pakpour et al 2014). …”
Section: Santa Clara Strength Of Religion Faith (Scsorf)mentioning
confidence: 99%
“…The SCSF correlates highly with the original instrument from which it is derived (r=0.95), which has excellent reliability (Storch, Roberti, Bravata, et al, 2004). The Persian translation of the SCSF is also reliable (Cronbach's α= 0.88; Pakpour, Saffari, & Zeidi 2014). In the present sample reliability of the SCSF was excellent (Cronbach's α=0.99).…”
Section: Methodsmentioning
confidence: 53%